(untitled) (Global Journal of Management and Business Research, 2020)
The demand for project effectiveness in its early phase to enhance the success rate is increasing among project management professionals. Several success factors had been studied in the last decades to determine the issue of project success. However, the practice of determining the success of a project based exclusively on the criteria of time, cost, and quality is no longer relevant and deemed out-dated.